Importance of the rhythm method - Lavergne, Julio (2015)
The importance of the rhythm method for us is because it is the only contraceptive method that the Catholic Church can be used for family planning. In March 1964, the present Pope Paul VI promised that the Church re-examine in depth the regulation of births. Studies of the theoretical effectiveness of the rhythm method with a statistical model show that the risk of conception per menstrual cycle decreases proportionally to the increase in the number of days of abstinence and increases in proportion to the contribution of the pre-ovulatory phase of the variation of the menstrual cycles. Therefore, as the Ogino formula requires three days of abstinence, it marks a period of eight days fertility theoretically offers greater protection estimated at 90% for 5-10 years. The mathematical probabilities for spacing births to 18 months (the likely event of those who use the rhythm method) requires a safety factor of 93%, which is only achieved by limiting the number of intercourse to 3 or 4 per month, which does not it is the reality in young marriages. That's why, with the use of the rhythm method have high failure rates, for example 14.5 (Rock) for 100 years long. These values have dropped to 8.3 (Lanctot) using the formula C-19 to mark the last day of the period of relative security in post menstrual period, and the use of thermal graph to determine the beginning of the period that absolute security It begins on the fourth day of rise in basal temperature.